3D interactive visualization using image color distribution - Lee, Chaelin; Seo, Sanghyun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Technologies related to image processing such as transforming the atmosphere of images or adding effects to images have been making rapid progress owing to the recent advancement of media.Methods/Statistical analysis: We need to devise methods to easily identify color composition and distribution in 3D space. This study introduces a method of visualizing the color distribution in 3D using standard color models so that the distribution pattern of color information in images can be easily understood.Findings: The distribution of colors that make up these images provides people with various stimuli and cognitive information. In order to convert images according to the user's intention in image manipulation research, the process of analyzing the images is very important, yet it is also significant to confirm that they have been converted as intended.Improvements/Applications: Our proposed method enables the user to intuitively understand and recognize color information of image.Â Â
Keywords: Information Visualization; Color Distribution; 3D Visualization; Color Model; Info-Graphic